Function of glycogen synthase kinase3 in embryogenesis of Dermanyssus gallinae - Meng, Jiali; Wang, Bohan; Qi, Xiaoxiao; Wang, Penglong; Liu, Boxing; Liu, Qi; Sun, Weiwei; Pan, Baoliang (Veterinary parasitology, 2023)
In the life cycle of Dermanyssus gallinae, the embryo is a developmental stage that does not require blood meals, but needs glucose to produce adenosine triphosphate (ATP) through glycolysis or oxidative phosphorylation, providing energy for embryonic development. Glycogen synthase kinase 3 (GSK3), belonging to the serine/threonine kinase family, is a key enzyme involved in glycogen metabolism in many eukaryotes, but not be described in D. gallinae. The present study was conducted to explore the role of Dg-GSK3 in the embryogenesis of D. gallinae. The results of qPCR showed that Dg-GSK3 mRNA was expressed in different development stages of D. gallinae embryos. RNA interference (RNAi) was performed on the female mites and eggs by immersion, and it was found that lowering GSK3 expression level could significantly decrease the female egg laying rate and egg hatching rate (P < 0.05). Some eggs became shrunken and shriveled in appearance. The fecundity of female D. gallinae obtained from the rDg-GSK3-immunized group of chickens (2.56 ± 0.35 eggs per mite, P < 0.0001) decreased significantly from that of the control group (3.49 ± 0.35). The oviposition rate of rDg-GSK3-immunized group (75.94 ± 7.28 %, P = 0.0003）was significantly lower that of the control group (89.69 ± 2.63 %). In conclusion, Dg-GSK3 is a crucial gene during the embryogenesis of D. gallinae, which can affect both the female fecundity and the egg hatching, which help us understand the function of GSK3 gene in the embryogenesis of mites. •Identification, cloning and sequencing of Dg-GSK3 gene.•Dg-GSK3 plays a vital role in the survival of Dermanyssus gallinae.•Recombinant Dg-GSK3 is a promising vaccine candidate against Dermanyssus gallinae.